(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
AMOS Y. MASSELE Department of Clinical Pharmacology, Muhimbili University, College of Health Sciences, P.O. Box 65010, Dar-es-Salaam, Tanzania A prospective survey of prescribing patterns at twenty antenatal clinics in Dar-es-Salaam, Tanzania, was carried out by trained research assistants in order to document the prescribing patterns of antenatal care providers. A total of 600 prescriptions were collected, recorded using WHO/DAP forms and analyzed. The number of drugs per prescription was 0-5 percentage of encounters with injection and antibiotic prescribed 22% and 20.1% respectively. Percentage of drugs prescribed by generic name was 77.6%. These and other related findings are discussed.